Congenitally corrected transposition of the great arteries (CCTGA). Issue 6 (9th June 2021) - Grech, Neil; Borg, Alexander; Sammut, Mark Adrian; Caruana, Maryanne
Abstract : A 33-year-old man presented with a 3-week history of breathlessness and cough. He disclosed that he was informed regarding a heart defect as a child in his home country but was unaware of its nature and was never followed up. Examination revealed a pansystolic murmur (loudest at the apex), a hyperdynamic, displaced apex, and pulmonary oedema. An ECG showed atrial fibrillation with a regular broad-complex ventricular rhythm. Following electrical cardioversion, the ECG revealed complete heart block, therefore explaining the regular atrial fibrillation. An urgent transthoracic echocardiography (TTE) confirmed the anatomy of congenitally corrected transposition of the great arteries (CCTGA) with torrential tricuspid regurgitation and impaired systemic right ventricle. Cardiac MRI identified a ventricular septal defect which was not visible on TTE. The patient showed a transient improvement following fluid offloading and ACE inhibition, with a more definitive improvement after cardiac resynchronisation therapy (CRT).